Effect of nano-SiO2 on the alkali-activated characteristics of spent catalyst metakaolin-based geopolymers. (15th July 2017) - Lo, Kang-Wei; Lin, Kae-Long; Cheng, Ta-Wui; Chang, Yu-Min; Lan, Ju-Ying
Highlights: Increasing nano-SiO2 content can improve the workability of geopolymer. Nano-SiO2 addition level was 0.5%, the pore volume became relatively denser. This band shifted toward low wavenumbers with increase in nano-SiO2 addition. Application of NS to a geopolymer enhanced its compactness and strength. Abstract: The effects of the nano-SiO2 (NS) addition levels (0.5–2%) and replacement levels of spent catalyst (0–20%) in a geopolymer were analyzed quantitatively. The initial and final setting time of spent catalyst metakaolin-based geopolymers (MKGP) with a 5% spent catalyst substitution at a constant addition of 0.5% NS were 201 and 270 min, respectively. The compressive strength of these geopolymers after 56 days of curing age was 71.10 MPa. Adding 2% NS substantially increased the compressive strength of the samples, and the high energy increases the speed and degree of polymerization. The percentage of mesopores was 84%. The Fourier transform infrared spectra of the geopolymers contained a distinct intensity band at 1300–900 cm −1, associated with the Si–O–T asymmetric vibration. The geopolymer with the optimal spent catalyst replacement level and NS addition level contained more structural dener beneficial to structure development. In summary, the application of NS to a geopolymer enhanced its compactness and strength.